Determination of Sarcosine in Urine of Patients with Prostate Cancer Diagnosis - Zollner, Andrea (Jihočeská univerzita, 2011)
In this thesis, the biochemistry and analysis of Sarcosine, Glycine and Alanine was reviewed. Moreover, a novel method for their determination in urine by means of reversed-phase liquid chromatography was examined and evaluated.
Determination of Sarcosine in Urine of Patients with Prostate Cancer Diagnosis
Keywords: Amino Acid Analysis; Sarcosine; Glycine; RP-HPLC; Amino Acid Analysis; Sarcosine; Glycine; RP-HPLC